Pengaruh Kepribadian, Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Boyolali - Safitri, Leni; Sutarno (Teewan Journal Solutions, 2025)
This study aims to investigate the extent to which personality, workload, and work environment contribute to employee performance at the Population and Civil Registration Office of Boyolali Regency. The data used in this study is quantitative data obtained directly from primary sources. All employees at the Population and Civil Registration Office of Boyolali Regency were the subject of this research. The sampling technique used was a census, involving all 35 employees. Data collection was done through direct observation of employee activities. Data analysis using multiple linear regression with the help of SPSS software showed a significant relationship between the independent variables (personality, workload, work environment) and the dependent variable (employee performance). The results of this study indicate that factors such as personality, workload, and work environment have an important influence on employee performance at the Population and Civil Registration Office of Boyolali Regency.